The Development of AISSEND: An Observation Tool to Assess Inclusive Practices - Keeley, Randa G.; Alvarado-Alcantar, Rebecca; Keeley, David W. (Journal of the American Academy of Special Education Professionals, 2020)
This article details the development and statistical validation of the diagnostic, observational tool Assessment of the Inclusion of Students with Special Educational Needs and Disabilities (AISSEND) designed to measure the type, frequency, and duration of inclusive practices implemented within an inclusion classroom. The goal of the research team was to develop a valid and reliable tool for measuring the inclusivity of a classroom that would be practical, reliable, and could be implemented across a school district on a large scale. Based on multiple methods of statistical analysis the AISSEND was determined to have face validity for measuring the inclusivity of a classroom.